2017
DOI: 10.26687/archnet-ijar.v11i3.1398
|View full text |Cite
|
Sign up to set email alerts
|

Smart Cities and Heritage Conservation: Developing a Smartheritage Agenda for Sustainable Inclusive Communities

Abstract: Keywords Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
9
0
4
Order By: Relevance
“…A busca por investimentos faz com que essa pauta entre na agenda dos governos locais e gere uma corrida por projetos de transformação do transporte público, edifícios, saúde, educação, turismo, e outros componentes urbanos em smart. Resultado disso, é a elaboração dos rankings especializados que se propõem a definir quais são as cidades mais inteligentes do mundo, cada ranking com seu universo amostral, metodologia e critérios (RIGANTI, 2017).…”
Section: O Discurso E a Prática Do Fenômeno Smart Cityunclassified
See 3 more Smart Citations
“…A busca por investimentos faz com que essa pauta entre na agenda dos governos locais e gere uma corrida por projetos de transformação do transporte público, edifícios, saúde, educação, turismo, e outros componentes urbanos em smart. Resultado disso, é a elaboração dos rankings especializados que se propõem a definir quais são as cidades mais inteligentes do mundo, cada ranking com seu universo amostral, metodologia e critérios (RIGANTI, 2017).…”
Section: O Discurso E a Prática Do Fenômeno Smart Cityunclassified
“…A preservação desse patrimônio nas cidades contemporâneas, assim, é uma pauta de importância indiscutível. Riganti (2017) relata, no entanto, que apesar da sua relevância, o patrimônio cultural nas cidades enfrenta uma pressão excessiva que o torna cada vez mais frágil. A poluição, a chuva ácida, a falta de políticas governamentais voltadas para a sua valorização, e as calamidades urbanas são alguns dos fatores citados pela pesquisadora.…”
Section: O Desafio Da Preservação Do Patrimônio Cultural Em Ambientes Urbanosunclassified
See 2 more Smart Citations
“…They examined the way in which the immersion of Virtual Reality (VR) affects spatial perception within the design process in the architectural design studio. The article of Patrizia Riganti, "Smart Cities and Heritage Conservation: Developing a Smartheritage Agenda for Sustainable Inclusive Communities" (Riganti, 2017), discussed advancements in Information Communication Technologies (ICT) for cultural heritage preservation highlighting the potential of virtual environments to assess the impacts of heritage policies on urban development while using virtual globes and crowdsourcing to support the participatory valuation and management of cultural heritage assets. On the other hand, the article on Virtual Platforms for Heritage Preservation in the Middle East: The Case of Medieval Cairo" (Abdelmonem et al, 2017), reported on a research process to investigate and incorporate a cultural-feed into digital platforms of Virtual Heritage, analysing current practices and projects of the virtual heritage technologies.…”
Section: On Architectural Education and Design Studio Teaching Practices Marta Masdéu And Josepmentioning
confidence: 99%